2020
DOI: 10.3390/cancers12092368
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy for Colon Cancer

Abstract: Glioblastoma multiforme (GBM) is the most common and devastating type of primary brain tumor, with a median survival time of only 15 months. Having a clinically applicable genetic biomarker would lead to a paradigm shift in precise diagnosis, personalized therapeutic decisions, and prognostic prediction for GBM. Radiogenomic profiling connecting radiological imaging features with molecular alterations will offer a noninvasive method for genomic studies of GBM. To this end, we analyzed over 3800 glioma and GBM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In multiple myeloma, high expression of FNDC3A can lead to ROS accumulation, ATP deficiency and cell death in multiple myeloma cells. VEGFA can be used as a prognostic biomarker for head and neck squamous cell carcinoma, esophageal squamous cell carcinoma, glioblastoma and papillary thyroid carcinoma (He et al, 2020;Stuchi et al, 2020;Yang et al, 2020;Zheng and Tao, 2020). Downregulation of VEGFA expression can inhibit the proliferation, angiogenesis and metastasis of osteosarcoma cells, ovarian cancer and lung squamous cell carcinoma (Chen et al, 2020a;Chen et al, 2020b;Li et al, 2020;Qin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In multiple myeloma, high expression of FNDC3A can lead to ROS accumulation, ATP deficiency and cell death in multiple myeloma cells. VEGFA can be used as a prognostic biomarker for head and neck squamous cell carcinoma, esophageal squamous cell carcinoma, glioblastoma and papillary thyroid carcinoma (He et al, 2020;Stuchi et al, 2020;Yang et al, 2020;Zheng and Tao, 2020). Downregulation of VEGFA expression can inhibit the proliferation, angiogenesis and metastasis of osteosarcoma cells, ovarian cancer and lung squamous cell carcinoma (Chen et al, 2020a;Chen et al, 2020b;Li et al, 2020;Qin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This article is limited to gold compounds acting on human CRC cell lines, which might poorly represent the clinical disease. However, especially in CRC surgical treatment, neoadjuvant and adjuvant therapy is applied to reduce the micrometastatic area, and in this context, cell-based assays, especially clonogene assays, can mimic the in vivo situation [ 35 ]. We are observing a significant increase in publications on gold complexes.…”
Section: Scope and Limitationsmentioning
confidence: 99%
“…In context of CRC therapy, the clinical prospective data on neoadjuvat therapy is limited—patients can benefit from these treatments [ 35 ], however the limitations are side effects such as neuropathy induced by oxaliplatin—that force for the invention of better and safer alternatives, such as other metallodrugs, including gold complexes [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In biomedical research, there is an active area of interest in novel treatment strategies that can be used to treat locally advanced disease in CRC. In this regard, an increasing body of evidence has shown that neoadjuvant chemotherapy (defined as chemotherapy administered to treat tumors before surgical resection) is able to reduce tumor size, facilitate resection, and improve completion rates in CRC 4 , [5] , [6] , 7 . The standard of care in neoadjuvant chemotherapy (NAC) consists in the use of maximum-tolerated doses (MTDs) of a cytotoxic drug.…”
Section: Introductionmentioning
confidence: 99%